The paradox of autoimmunity and autoinflammation in inherited neutrophil disorders – in search of common patterns - Krzyzanowski, Damian; Oszer, Aleksandra; Madzio, Joanna; Zdunek, Maciej; Kolodrubiec, Julia; Urbanski, Bartosz; Mlynarski, Wojciech; Janczar, Szymon (Frontiers in Immunology, 2023)
Congenital defects of neutrophil number or function are associated with a severe infectious phenotype that may require intensive medical attention and interventions to be controlled. While the infectious complications in inherited neutrophil disorders are easily understood much less clear and explained are autoimmune and autoinflammatory phenomena. We survey the clinical burden of autoimmunity/autoinflammation in this setting, search for common patterns, discuss potential mechanisms and emerging treatments.